A test of risk clientele effects via an examination of trading volume response to earnings announcements - Kross, William; Ha, Gook-Lak; Heflin, Frank (Journal of Accounting and Economics, 1994)
This research investigates whether volume reactions to a public announcement are related to changes in the risk of securities (i.e., investors undertake portfolio rebalancing when the risk of their portfolio becomes misaligned with their respective risk preferences). Our results document that an average (40 percent) change in beta is associated with a 0.10 percent increase in the number of shares traded in a ten-day period around the earnings announcement. Although risk clientele effects are less important than information effects, they are empirically significant.